Placenta Previa and Pre-Eclampsia: Analyses of 1645 Cases at Medani Maternity Hospital, Sudan - Adam, Ishag; Haggaz, AbdElrahium D.; Mirhagni, Omer A.; Elhassan, Elhassan M. (Frontiers in Physiology, 2013)
A retrospective case- control study was conducted to investigate the risk factors for pre-eclampsia -including the protective effect of placenta previa -at Medani Maternity Hospital, Sudan. Medical files of the patients during the period 2003 to 2010 were reviewed for age, parity, education level, prenatal care, placenta previa and hemoglobin level. Women with pre-eclampsia were the cases, and women with normal pregnancy were the controls. There were 54339 singleton deliveries and 1765 women with pre-eclampsia in the hospital, giving the incidence of pre-eclampsia of 3.2%. The risk factors for pre-eclampsia were; women with age > 35 year (OR= 1.4, 95% CI: 1.1-1.8), primiparity (OR = 3.3, 95% CI: 2.7–4.0), para > 5 (OR= 3.1, 95% CI: 2.4–4.0) and anemia (OR= 3.3, 95% CI: 2.8–3.9). The risk of pre-eclampsia was inversely increased with education level and prenatal care attendance. The prevalence of placenta previa was 0(0%) and 55 (3.3%), P< 0.001 in pre-eclamptic and control women, respectively. Placenta previa was a significant protective factor of pre-eclampsia (OR= 0.3, 95% CI: 0.1–0.7). Although, the socio-demographic risk factors for pre-eclampsia observed among women at Medani hospital were similar to those found in other settings; placenta previa was associated with decreased incidence of pre-eclampsia.